Interaction between cannabis consumption and childhood abuse in psychotic disorders: preliminary findings on the role of different patterns of cannabis use. Issue 2 (12th November 2015) - Sideli, Lucia; Fisher, Helen L.; Murray, Robin M.; Sallis, Hannah; Russo, Manuela; Stilo, Simona A.; Paparelli, Alessandra; Wiffen, Benjamin D.R; O'Connor, Jennifer A.; Pintore, Sonia; Ferraro, Laura; La Cascia, Caterina; et al.
Abstract: Aim: Several studies have suggested that lifetime cannabis consumption and childhood abuse synergistically contribute to the risk for psychotic disorders. This study aimed to extend existing findings regarding an additive interaction between childhood abuse and lifetime cannabis use by investigating the moderating role of type and frequency of cannabis use. Methods: Up to 231 individuals presenting for the first time to mental health services with psychotic disorders and 214 unaffected population controls from South London, United Kingdom, were recruited as part of the Genetics and Psychosis study. Information about history of cannabis use was collected using the Cannabis Experiences Questionnaire. Childhood physical and sexual abuse was assessed using the Childhood Experience of Care and Abuse Questionnaire. Results: Neither lifetime cannabis use nor reported exposure to childhood abuse was associated with psychotic disorder when the other environmental variable was taken into account. Although the combination of the two risk factors raised the odds for psychosis by nearly three times (adjusted OR = 2.94, 95% CI: 1.44–6.02, P  = 0.003), no evidence of interaction was found (adjusted OR = 1.46, 95% CI: −0.54 to 3.46, P  = 0.152). Furthermore, the association of high‐potency cannabis and daily consumption with psychosis was at least partially independent of the effect of childhood abuse. Conclusions: The heavy use of high‐potency cannabis increases the risk of psychosis but, in addition, smoking of traditional resin (hash) and less than daily cannabis use may increase the risk for psychosis when combined with exposure to severe childhood abuse.